PSYCHOLOGICAL ANALYSIS ON THE MAIN CHARACTER PERSONALITY IN THE SHORT STORIES BY ROALD DAHL - Pardi Bilalia (British (Jurnal Bahasa dan Sastra Inggris), 2018)
This research is aimed to analyze the main character personality short stories by Roald Dahl  as Depicted in her Short Stories. In conducting this research, the researcher applies the qualitative descriptive method. The researcher uses documentation as the technique of collecting data. All the necessary data which related to the research are gathered by doing several steps. The first tep is the researcher selects the short stories by Roald Dahl. The second step is the researcher gathers the literary reference that related to psychological approach. From the analysis the researcher finds that anyone who lives in this world will not be separated from its basic needs,  psychological needs, and self fulfillment need. Like food, water, rest, intimate relationships, and achieving one’s full potential.   Keywords: Personality, Psychology, Motivation